This preview shows page 1. Sign up to view the full content.
Unformatted text preview: N and solve for g '( y ): 3 3 2 2 x g y x y g y y + = + = ( ) ( ) We integrate to find g ( y ): g y g y y dy y C ( ) ( ) = = = + 2 2 1 Substitute this into the first expression containing g ( y ) to obtain F ( x , y ): F x y x xy g y x xy y C ( , ) ( ) = + + = + + + 2 2 2 1 3 3 If an initial condition is given, the value of C 1 can be found, yielding a particular solution. In this case, an initial condition was not given. THE ANSWER The general solution is then written in this form, absorbing the value of C 1 into C . x xy y C 2 2 3 + + = Tom Penick tomzap@eden.com www.teicontrols.com/notes October 24, 1997...
View
Full
Document
This note was uploaded on 03/29/2008 for the course MATH 308 taught by Professor Comech during the Spring '08 term at Texas A&M.
 Spring '08
 comech

Click to edit the document details